DEVELOPMENT OF LKPD PROBLEM BASED LEARNING MODEL BASED ON COGNITIVE CONFLICT IN ADITIVE AND ADDICTIVE MATERIALS OF CLASS VIII SMP/MTs - RESTU VANNI DEZOLA; Hardeli Hardeli (Universe, 2020)
To produce Students Worksheet Using Problem Based Learning Based on Cognitive Conflict at Additive and Addictive Substance Material and explain the level of validity and practicality of worksheet. The type of research is used Research and Development or Research and Development (R&D) using the Plomp Development model which consists of three stages: Preliminary research, prototyping stage, and assessment stage. The research instrument used the form of a questionnaire for validity sheet and practicality of Problem Based Learning Based on Cognitive Conflict at Additive and Addictive Substance Material, it was validated by 4 validators consisting of 2 lecturers of Natural Science FMIPA UNP, and 2 teachers from SMP N 31 Padang. The practicality test was conducted with science teachers of SMP N 31 Padang and students of class VIII SMP N 31 Padang. This research produced a problem based learning based on cognitive conflict on additive and addictive with a mean moment of kappa is a very high level of validity. The result of the teacher practicality test and the practicality test of the students obtained an average of kappa moments sequentially with very high degree of practicality. To produce Students Worksheet Using Problem Based Learning Based on Cognitive Conflict at Additive and Addictive Substance Material and explain the level of validity and practicality of worksheet. The type of research is used Research and Development or Research and Development (R&D) using the Plomp Development model which consists of three stages: Preliminary research, prototyping stage, and assessment stage. The research instrument used the form of a questionnaire for validity sheet and practicality of Problem Based Learning Based on Cognitive Conflict at Additive and Addictive Substance Material, it was validated by 4 validators consisting of 2 lecturers of Natural Science FMIPA UNP, and 2 teachers from SMP N 31 Padang. The practicality test was conducted with science teachers of SMP N 31 Padang and students of class VIII SMP N 31 Padang. This research produced a problem based learning based on cognitive conflict on additive and addictive with a mean moment of kappa is a very high level of validity. The result of the teacher practicality test and the practicality test of the students obtained an average of kappa moments sequentially with very high degree of practicality. Keywords: Students Worksheets, Problem Based Learning Based On Cognitive Conflict, Additive and Addictive